2014
DOI: 10.1186/1756-0500-7-451
|View full text |Cite
|
Sign up to set email alerts
|

Identification of appropriate reference genes for qPCR studies in Staphylococcus pseudintermedius and preliminary assessment of icaA gene expression in biofilm-embedded bacteria

Abstract: BackgroundQuantitative PCR is rapidly becoming the standard method for analyzing gene expression in a wide variety of biological samples however it can suffer from significant error if stably expressed reference genes are not identified on which to base the analysis. Suitable reference genes for qPCR experiments on Staphylococcus pseudintermedius have yet to be identified.ResultsThree reference genes in S. pseudintermedius were identified and validated from a set of eight potential genes (proC, gyrB, rplD, rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…MRSP isolates are able to produce biofilm, and MRSP ST71 isolates, in particular, are better biofilm producers than other MRSP clones (5,6). The icaA gene can be significantly upregulated in biofilm samples, suggesting a role in the biofilm production by S. pseudintermedius (7). The ability to form biofilm may play an important role in the pathophysiology of bacterial infections and can be related to survival and persistence of S. pseudintermedius, namely, MRSP, in the environment (5,6).…”
Section: Ethicillin-resistant Staphylococcus Pseudintermedius (Mrsp)mentioning
confidence: 97%
“…MRSP isolates are able to produce biofilm, and MRSP ST71 isolates, in particular, are better biofilm producers than other MRSP clones (5,6). The icaA gene can be significantly upregulated in biofilm samples, suggesting a role in the biofilm production by S. pseudintermedius (7). The ability to form biofilm may play an important role in the pathophysiology of bacterial infections and can be related to survival and persistence of S. pseudintermedius, namely, MRSP, in the environment (5,6).…”
Section: Ethicillin-resistant Staphylococcus Pseudintermedius (Mrsp)mentioning
confidence: 97%
“…Relative quantification of gene expression was performed on a Light Cycler 480 (Roche Applied Science, Mannheim, Germany). The staphylococcal housekeeping genes gyrB, rho and tpiA, coding for DNA gyrase subunit B, transcription termination factor rho and triosephosphate isomerase tpiA, respectively, were used as internal reference genes (Theis et al, 2007;Crawford et al, 2014;Sihto et al, 2014). The TaqMan Fast Advanced Master Mix 23 (Thermo Fisher Scientific) was used according to the manufacturer's instructions, duplicates of the reaction were set up manually in a reaction volume of 15 ml.…”
Section: Quantification Of Sepa Ecp and Esp Expressionmentioning
confidence: 99%
“…Primers available for reference genes and for icaA from a previous study were used . Gene sequences for icaB , icaC , icaD , spsE , ebpS , mecA , atl , agrA , and agrB were examined in S. epidermidis and S. aureus in previous studies, and analogous sequences were identified in S. pseudintermedius for evaluation in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Primers available for reference genes and for icaA from a previous study were used. 25 Gene sequences for icaB, icaC, icaD, spsE, ebpS, mecA, atl, agrA, and agrB were examined in S. epidermidis and S. aureus in previous studies, 12,13,15,[26][27][28][29] and analogous sequences were identified in S. pseudintermedius for evaluation in this study. Primers were designed (Table S1) using a combination of GeneRunner software version 3.05 (Hasting Software, Inc, Hasting, NY) and the National Centre for Biotechnology Information online primer designing tool (http://www.ncbi.nlm.nih.gov/tools/ primer-blast/) using gene sequences for 2 strains of S. pseudintermedius (strains ED99 and HKU10-03) available from Genbank (http://www.ncbi.nlm.nih.gov/genbank/).…”
Section: Primer Design and Determination Of Pcr Efficiencymentioning
confidence: 99%
See 1 more Smart Citation